A review of the immunogenetics of Stevens-Johnson syndrome and toxic epidermal necrolysis - Ayca Kocaaga; Mustafa Kocaaga (Global Medical Genetics)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are very rare dermatologic disorders characterized by extensive detachment of the epidermis. Although some drugs, infectious agents, HLA genes, malignancy and connective tissue diseases are thought to play a role in the development of the disease, the pathogenesis has not been fully elucidated. Type IV hypersensitivity reactions are thought to be the underlying cause of these diseases. Inflammatory changes such as purulent erosion, ulcers and crusting can be seen in the gastrointestinal system, urinary tract and genital mucosa. Some immunologic biyomarkers like as HLA-B* 1502, Granulysin and CCL-27 are used in clinical diagnosis, prognosis, treatment, and personalized new drug development that could further explain the pathogenesis of SJS and TEN. This review focuses on the pathophysiology of the SJS and TEN and presents it in light of current data on this subject. We recommend further in vivo and in vitro studies to unravel the underlying immunological mechanisms to determine appropriate intervention strategies.